Pulmonary Artery Aneurysm as a Cause of Massive Hemoptysis: Diagnosis and Management - Peter Corr (Case Reports in Radiology)
Massive hemoptysis is a life-threatening medical emergency. Prompt radiological diagnosis and management are essential. I present a case of an inflammatory pulmonary aneurysm (Rasmussen aneurysm) from active pulmonary tuberculosis. This is an uncommon cause for massive hemoptysis which was successfully treated by endovascular coiling.